School attendance and daily respiratory symptoms in children: influence of moisture damage. (28th June 2016) - Casas, L.; Espinosa, A.; Pekkanen, J.; Asikainen, A.; Borràs‐Santos, A.; Jacobs, J.; Krop, E. J. M.; Täubel, M.; Hyvärinen, A.; Heederik, D.; Zock, J.‐P.
Abstract: We investigated the effect of weekends and school holidays on the daily frequency and severity of respiratory and other symptoms among children attending schools with (index) or without (reference) moisture damage in Spain, the Netherlands, and Finland. Throughout 1 year, parents of 419 children with a respiratory condition attending index (n=15) or reference (n=10) primary schools completed three symptom diaries. We assessed associations between lower respiratory tract, upper respiratory tract or allergy, and other symptom scores and school day, weekend, or summer holiday using mixed regression models stratified by country and moisture damage. We evaluated interactions between moisture damage and type of day. We combined country‐specific estimates (incidence rate ratios [IRRs] and 95% confidence interval [CI]) in meta‐analyses. Symptom scores were lower during weekends and holiday. Lower respiratory tract symptoms were statistically significantly less common during holiday with strongest effect in index schools (IRR=0.7; CI=0.6–0.8). Reporting of other symptoms was more reduced during holiday in index (IRR=0.6; CI=0.4–0.9) than in reference (IRR=0.95; CI=0.8–1.2) schools (interaction P <.01). In conclusion, symptoms were less frequent and/or severe during summer holiday and weekends. This pattern was stronger among children attending moisture‐damaged schools, suggesting potential improvement in moisture damage‐related symptoms during school breaks.